Anmeldelser - Giurchescu, Anca (Danish Yearbook of Musicology, 1995)
Review of: Owe Ronstrom: Att gestalta ett ursprung. En musiketnologisk studie av dansande och musicerande bland jugoslaver i Stockholm. (Giving form to an origin. An ethno-musicologic study on dancing and music-making among the Yugoslavs in Stockholm). Institutet för folklivsforskning, Stockholm 1992.